Effect of a bioresorbable membrane on postoperative adhesions and wound healing - Bülbüller, N; Sapmaz, E; Akpolat, N; Üstündag, B; Kirkil, C (Sci Printers & Publ Inc, 2003)
OBJECTIVE: To study the effect of Seprafilm (Genzym Corporation, Cambridge, Massachusetts), a biosorbable membrane, on adhesion formation and injury recovery. STUDY DESIGN: Twenty female Wistar-albino rats were divided into two groups of 10 each. The right uterine horns of all rats were incised longitudinally and then stitched. While no procedure was conducted in group I (control group), in group II (Seprafilm group) this incision line was wrapped with Seprafilm. The rats were re-operated on day 7 after the first operation. The results were assessed using the Mann-Whitney U (MWU) test, and P < .05 was considered significant. RESULTS: The adhesion score in group I was higher than in group II (3.6 +/- 0.1 vs. 0.3 +/- 0.1; P = .000, MWU test). In the histopathologic examination performed to examine injury recovery, the measured bursting pressures and hydroxyproline levels were similar in the two groups. CONCLUSION: Seprafilm prevented postoperative adhesions without affecting injury recovery and thus can be used reliably.
Keywords: adhesions; wound healing; Seprafilm